The Transition From University to Work: The Positive Influence of Purpose in Life and Social Support - Karbainova, Daria; Barker, Erin T. (Canadian Journal of Counselling and Psychotherapy, 2022)
In the transition to adulthood, the common developmental task of progressing into the workforce is potentially challenging for many. This study aimed to investigate whether the presence of particular promotive factors would benefit emerging adults who are engaged in this task. Specifically, the authors used longitudinal multi-level modelling to test how purpose in life and perceived social support co-varied with satisfaction when it came to the pursuit of employment. University students in their last semester of undergraduate study (N = 103) were recruited to complete four surveys across a year following graduation. The results indicated that on occasions when participants had greater purpose in life and perceived social support, they experienced greater satisfaction with their employment situation. In addition, greater purpose in life—but not perceived social support—before graduation predicted greater average employment satisfaction across the year. These resilience factors may ease some of the strain related to this often difficult transition, by bolstering young people’s employment appraisal.